1996
DOI: 10.1021/jp9614355
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectra of Ni(CO)4 and Cr(CO)6 Revisited

Abstract: The electronic absorption spectra of Cr(CO)6 and Ni(CO)4 have been studied in detail using multiconfigurational perturbation theory based on a complete active space wave function (the CASSCF/CASPT2 approach). Calculated results for both excitation energies and oscillator strengths are reported. Based on the calculated results an assignment of the experimental absorption spectra is proposed. In both cases, the assignment is different from any previously published assignments. The most striking difference is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
137
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(152 citation statements)
references
References 30 publications
13
137
2
Order By: Relevance
“…Other TDDFT calculations with the ADF program on transition metal compounds are in progress. Of these, we just mention the TDDFT results for Cr(CO) 6 , 25,75,76 which reconfirm the assignments based on the CASPT2 69 and DFT-∆SCF 77 approaches, thus challenging the long-standing assignments by Beach and Gray 43,44 on the nature of the lowest excited states of these systems. The TDDFT results are, in this case, in much better agreement with the experimental and CASPT2 values than the ∆SCF results are.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Other TDDFT calculations with the ADF program on transition metal compounds are in progress. Of these, we just mention the TDDFT results for Cr(CO) 6 , 25,75,76 which reconfirm the assignments based on the CASPT2 69 and DFT-∆SCF 77 approaches, thus challenging the long-standing assignments by Beach and Gray 43,44 on the nature of the lowest excited states of these systems. The TDDFT results are, in this case, in much better agreement with the experimental and CASPT2 values than the ∆SCF results are.…”
Section: Resultsmentioning
confidence: 76%
“…In contrast to this, INDO/S CI 86 yields six of such states, CASSCF 69 yields zero (! ), and SECI yields two.…”
Section: Excitation Energies Of This Molecule Which Has T D Symmetrymentioning
confidence: 97%
See 1 more Smart Citation
“…A very clear example is Cr(CO) 6 , where we have recently found 48 precisely the same situation to apply: the ligand-field excited states are at R e at high energy, but they descend so rapidly upon Cr-CO bond lengthening that they very soon cross the lowest excited state, which has CT character at R e , so that the lowest excited state PEC becomes dissociative. Recent sophisticated CASSCF/ CASPT2 calculations of the optical spectrum of Cr(CO) 6 by Pierloot et al 49 provide support for this reassessment of the role of LF states in the photochemical metal-carbonyl dissociation process in that they show that the LF excited states of Cr(CO) 6 arescontrary to the original assignment by Beach and Gray 50 slocated rather high in the spectrum, the photodissociative lowest excited states having clear CT character at R e . IC960688+…”
Section: Discussionmentioning
confidence: 79%
“…26 Analysis of the bond length change in the ligand field excited state of [PtCl 3 (CO)] -showed that the metal-carbon distance increased by 0.18 Å. 10 All of the above bond length changes, with the exception of those in Mo(CO) 6 and W(CO) 6 , 24,25 occur in excited states assigned as primarily d-d in character. The picture that is emerging is that the changes in the metalcarbon bond lengths in ligand field excited states of metalcarbonyl complexes are between about 5% and 10% of the bond length.…”
mentioning
confidence: 99%